Battery pole piece, battery and electric device
By adjusting the particle size of active material in the battery electrode sheet according to the layer, the problem that traditional solid-state batteries are difficult to take into account both energy density, rate performance and cycling performance is solved, and efficient ion transmission and excellent battery performance are achieved.
Patent Information
- Application Number
- CN202311278545.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
AI Technical Summary
Traditional solid-state batteries are difficult to take into account high energy density, excellent rate performance and good cycle performance.
By designing a battery electrode sheet, the particle size of the active material of the active layer on both sides of the current collector is regulated according to the layer, so that the particle size of the active layer closer to the current collector is small and the particle size of the active layer far away from the current collector is large, so as to improve the ion transport capability.
It realizes the improvement of the battery's rate performance and cycle performance while maintaining high capacity, ensuring that both excellent rate performance and good cycle performance can still be achieved under high energy density systems.
Smart Images

Figure CN119725358A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a battery pole piece, a battery and an electrical device. Background Art
[0002] Solid-state batteries use non-flammable solid electrolytes to replace the flammable organic liquid electrolytes in traditional batteries, which greatly improves the safety of the batteries and is considered to be the new generation of batteries closest to industrialization. In addition to improving safety, solid-state batteries can better adapt to high-energy-density positive and negative electrode materials and reduce system weight, thereby achieving a simultaneous increase in energy density.
[0003] In traditional technology, in order to make the energy density of solid-state batteries equal to or even better than that of liquid lithium-ion batteries, it is necessary to increase the mass proportion of positive electrode active materials in the active layer and the surface capacity of the battery pole piece. However, this will lead to a decrease in the content of solid electrolyte in the active layer. Solid-state batteries transmit ions through solid electrolytes in the battery pole pieces. A decrease in the content of solid electrolytes will lead to a decrease in the conductivity of active ions such as lithium ions in the battery pole pieces. In addition, high surface capacity leads to an increase in pole piece thickness, thereby increasing the path and impedance of lithium ion transmission. These will lead to a decrease in the discharge capacity of solid-state batteries, and will also accelerate capacity decay and deteriorate cycle performance, making it difficult to take into account high energy density, excellent rate performance and good cycle performance.
[0004] Therefore, the traditional technology still needs to be improved. Summary of the invention
[0005] Based on this, the present application provides a battery electrode, a battery and an electrical device, so that the battery can improve the rate performance and cycle performance while maintaining a high capacity.
[0006] The present application is implemented through the following technical solutions.
[0007] In a first aspect of the present application, a battery pole piece is provided, the battery pole piece comprising a current collector and n active layers sequentially arranged on at least one side surface of the current collector; components of each active layer include active materials and solid electrolytes;
[0008] In any two adjacent active layers, the volume distribution particle size Dv50 of the active material in the active layer closer to the current collector is smaller than the volume distribution particle size Dv50 of the active material in the other active layer;
[0009] n is an integer greater than or equal to 2.
[0010] The study found that: under the condition that the particle size of the solid electrolyte is the same, the larger the particle size of the active material, the better the contact between the active material and the solid electrolyte, and the stronger the ion transmission capacity; when the particle size of the active material is smaller, the ion transmission path inside the active material is shorter, and the capacity exerted is higher.
[0011] Therefore, in the above-mentioned battery pole piece, the volume distribution particle size Dv50 of the active material in any two adjacent active layers is regulated so that the volume distribution particle size Dv50 of the active material in the active layer closer to the current collector is smaller than the volume distribution particle size Dv50 of the active material in the other active layer. Therefore, on the one hand, the volume distribution particle size Dv50 of the active material in the active layer closer to the current collector is made smaller, so as to give full play to the higher discharge capacity characteristics of the active material with smaller particles; on the other hand, the volume distribution particle size Dv50 in the active layer far away from the current collector, that is, the active layer closer to the electrolyte when used, is made larger, so as to give full play to the stronger ion transmission ability of the positive electrode composed of active materials with larger particles, so that active ions such as lithium ions can be quickly transmitted from the electrolyte to the entire composite battery pole piece. All aspects work together to improve the rate performance and cycle performance of the battery at the same time, and even in a high-capacity system, that is, a high-energy density system, it can still have both excellent rate performance and good cycle performance.
[0012] In some of the embodiments, in at least one layer of the active layer, the volume distribution particle size Dv50 of the active material is greater than the volume distribution particle size Dv50 of the solid electrolyte;
[0013] Optionally, in each active layer, the volume distribution particle size Dv50 of the active material is greater than the volume distribution particle size Dv50 of the solid electrolyte.
[0014] The volume distribution particle size Dv50 of the solid electrolyte and active material is further regulated to achieve synergistic compounding, thereby further improving the ion transport performance of the battery electrode.
[0015] In some embodiments, the volume distribution particle size Dv50 of the solid electrolyte in each active layer is less than or equal to 10 μm;
[0016] Regulate the particle size of the solid electrolyte to further optimize the ion transport performance of the battery electrode.
[0017] Optionally, the volume distribution particle size Dv50 of the solid electrolyte in each active layer is independently selected from 50 nm to 10 μm;
[0018] Further optionally, the volume distribution particle size Dv50 of the solid electrolyte in each active layer is independently selected from 50 nm to 5 μm.
[0019] Furthermore, the study found that the smaller the volume distribution particle size Dv50 of the solid electrolyte, the better the ion transmission capacity, especially when the volume distribution particle size Dv50 is not less than 5μm, the ion transmission capacity is more significantly optimized.
[0020] In some embodiments, the volume distribution particle size Dv50 of the active material in each active layer is less than or equal to 15 μm;
[0021] Optionally, the volume distribution particle size Dv50 of the active material in each active layer is independently selected from 100 nm to 15 μm;
[0022] Further optionally, the volume distribution particle size Dv50 of the active material in each active layer is independently selected from 100 nm to 10 μm.
[0023] In some embodiments, the absolute value of the difference in volume distribution particle size Dv50 of the active material in any two adjacent active layers is K, K≤12 μm;
[0024] 0.5μm≤K≤12μm;
[0025] Optionally, 0.5 μm≤K≤5 μm.
[0026] The difference in volume distribution particle size of the active materials in two adjacent active layers is further regulated, so that the larger particles of active materials and the smaller particles of active materials can further play a better synergistic compounding role.
[0027] In some embodiments, the battery electrode satisfies any one of the following conditions (1) to (2):
[0028] (1) In each active layer, the proportion of the active material is independently selected from: 70wt% to 99wt%;
[0029] Optionally, in each active layer, the proportion of the active material is independently selected from: 80wt% to 95wt%;
[0030] (2) In each active layer, the proportion of the solid electrolyte is independently selected from: 0.1wt% to 30wt%.
[0031] In some embodiments, the active layer satisfies at least one of the following conditions (3) to (4):
[0032] (3) The surface capacity of each active layer is independently selected from: 1 mAh / cm 2 ~3mAh / cm 2 ;
[0033] (4) The total surface capacity of the n-layer active layer is not less than 4 mAh / cm 2 ;
[0034] Optionally, the total surface capacity of the n-layer active layer is 4 mAh / cm 2 ~8mAh / cm 2 .
[0035] In some embodiments, the active layer satisfies at least one of the following conditions (5) to (6):
[0036] (5) The thickness of each active layer is independently selected from 20 μm to 60 μm;
[0037] (6) The total thickness of the n-layer active layer is 80 μm to 300 μm.
[0038] In some embodiments, the active layer satisfies at least one of the following conditions (7) to (8):
[0039] (7) The active material includes a positive electrode active material;
[0040] (8) The solid electrolyte includes at least one of an oxide solid electrolyte, a sulfide electrolyte and a halide electrolyte.
[0041] In some embodiments, the active layer satisfies at least one of the following conditions (9) to (10):
[0042] (9) The components of each active layer also include a conductive agent;
[0043] Optionally, in each active layer, the mass proportion of the conductive agent is independently selected from 0.1wt% to 5wt%;
[0044] (10) The components of each active layer also include a binder;
[0045] Optionally, in each active layer, the mass proportion of the binder is independently selected from 0.1wt% to 5wt%.
[0046] A second aspect of the present application provides a battery, comprising the battery electrode sheet of the first aspect.
[0047] According to a third aspect of the present application, there is provided an electrical device, wherein the electrical device comprises the battery according to the second aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:
[0049] Figure 1 is a schematic diagram of one embodiment of a battery;
[0050] Figure 2 yes Figure 1 Exploded diagram of
[0051] Figure 3 is a schematic diagram of an embodiment of a battery pack;
[0052] Figure 4 yes Figure 3 Exploded diagram of
[0053] Figure 5 is a schematic diagram of an embodiment of an electrical device in which a battery is used as a power source;
[0054] Figure 6 It is a schematic diagram of the structure of the positive electrode sheet in Example 1.
[0055] Description of reference numerals:
[0056] 1. Battery pack; 2. Upper box; 3. Lower box; 4. Battery; 41. Shell; 42. Electrode assembly; 43. Cover plate; 5. Electrical device; 421. Positive electrode sheet; 421a. Current collector; 421b. First positive electrode active layer; 421c. Second positive electrode active layer; 4211. Positive electrode active material. DETAILED DESCRIPTION
[0057] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0058] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0059] To sum up the above background, it is difficult for traditional solid-state batteries to achieve high energy density, excellent rate performance and good cycle performance.
[0060] The study found that the particle size of the active material affects its discharge capacity and ion transport. The smaller the particle, the shorter the lithium ion transport path inside the active material, and the higher the capacity that can be exerted. However, the contact between the small-particle active material and the electrolyte is not sufficient, the ion transport of the composed electrode is insufficient, and the ion conductivity of the electrode will decrease, resulting in a faster capacity decay of the battery. The larger the particle size of the active material, the higher the ion conductivity of the electrode, and the correspondingly improved battery cycle performance. However, due to the longer lithium ion transport path inside the large-particle active material itself, it limits the kinetics, and its discharge capacity is lower than that of the small-particle active material, resulting in a decrease in the battery discharge capacity and rate performance.
[0061] Further research found that ion conduction in the active layer close to the electrolyte side, that is, the part of the active layer away from the current collector surface, is a key step affecting battery performance. Based on this, after a lot of creative research, the battery pole piece in this application was obtained.
[0062] In one embodiment of the present application, a battery pole piece is provided, which includes a current collector and n active layers sequentially arranged on at least one side surface of the current collector; components of each active layer include active materials and solid electrolytes.
[0063] In any two adjacent active layers, the volume distribution particle size Dv50 of the active material in the active layer closer to the current collector is smaller than the volume distribution particle size Dv50 of the active material in the other active layer;
[0064] n is an integer greater than or equal to 2.
[0065] In the above-mentioned battery pole piece, the volume distribution particle size Dv50 of the active material in any two adjacent active layers is regulated so that the volume distribution particle size Dv50 of the active material in the active layer closer to the current collector is smaller than the volume distribution particle size Dv50 of the active material in the other active layer. Thus, on the one hand, the volume distribution particle size Dv50 of the active material in the active layer closer to the current collector is made smaller, so as to give full play to the higher discharge capacity characteristics of the active material with smaller particles; on the other hand, the volume distribution particle size Dv50 in the active layer far away from the current collector, that is, the active layer closer to the electrolyte when used, is made larger, so as to give full play to the stronger ion transmission ability of the active layer composed of active materials with larger particles, so that active ions such as lithium ions can be quickly transmitted from the electrolyte to the entire composite battery pole piece. All aspects work together to improve the rate performance and cycle performance of the battery at the same time, and even in a high-capacity system, that is, a high-energy density system, it can still have both excellent rate performance and good cycle performance.
[0066] In the present application, the above-mentioned Dv50 is: in the particle size-volume cumulative distribution curve, the particle size corresponding to 50% of the volume distribution can be obtained based on the volume cumulative distribution curve. As an example, it can be carried out with reference to the relevant standards of GB / T19077-2016 / ISO 13320:2009, and can be conveniently measured using a laser particle size analyzer, such as the Mastersizer 2000E laser particle size analyzer of Malvern Instruments Ltd. in the United Kingdom.
[0067] Refer to GB / T19077-2016 / ISO 13320:2009 standard process, the specific test process is as follows:
[0068] Take an appropriate amount of the sample to be tested and add it to deionized water. The sample concentration should be 8% to 12% shading. Ultrasonicate for 5 minutes to ensure that the sample is completely dispersed. Then measure the sample according to GB / T19077-2016 / ISO13320:2009 standard.
[0069] The frequency of ultrasound is 53KHz and the power is 120W.
[0070] It can be understood that the current collector has two surfaces opposite to each other in its thickness direction, and n active material layers are sequentially arranged on any one or both of the two opposite surfaces of the current collector.
[0071] In some of the embodiments, in at least one active layer, the volume distribution particle size Dv50 of the active material is larger than the volume distribution particle size Dv50 of the solid electrolyte.
[0072] Optionally, in each active layer, the volume distribution particle size Dv50 of the active material is greater than the volume distribution particle size Dv50 of the solid electrolyte.
[0073] The volume distribution particle size Dv50 of the solid electrolyte and active material is further regulated to achieve synergistic compounding, thereby further improving the ion transport performance of the battery electrode.
[0074] In some of the embodiments, the volume distribution particle size Dv50 of the solid electrolyte in each active layer is less than or equal to 10 μm.
[0075] Regulate the particle size of the solid electrolyte to further optimize the ion transport performance of the battery electrode.
[0076] Optionally, the volume distribution particle size Dv50 of the solid electrolyte in each active layer is less than or equal to 5 μm.
[0077] Furthermore, the study found that the smaller the volume distribution particle size Dv50 of the solid electrolyte, the better the ion transmission capacity, especially when the volume distribution particle size Dv50 is less than 5μm, the ion transmission capacity is more significantly optimized.
[0078] Optionally, the volume distribution particle size Dv50 of the solid electrolyte in each active layer is independently selected from 50 nm to 10 μm.
[0079] Optionally, the volume distribution particle size Dv50 of the solid electrolyte in each active layer is independently selected from 50 nm to 5 μm.
[0080] In the above “50nm~10μm”, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and the following point values: 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 800nm, 850nm, 900nm, 950nm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm; or a range consisting of any two values, for example: 50nm~10μm, 100nm~10μm, 200nm~10μm, 300nm~10μm m~10μm, 400nm~10μm, 500nm~10μm, 600nm~10μm, 700nm~10μm, 800nm~10μm, 900nm~1 0μm, 50nm~5μm, 100nm~5μm, 200nm~5μm, 300nm~5μm, 400nm~5μm, 500nm~5μm, 600nm~5 μm, 700nm~5μm, 800nm~5μm, 900nm~5μm, 50nm~3μm, 100nm~3μm, 200nm~3μm, 300nm~3μm m, 400nm~3μm, 500nm~3μm, 600nm~3μm, 700nm~3μm, 800nm~3μm, 900nm~3μm, 1μm~3μm.
[0081] In some embodiments, the volume distribution particle size Dv50 of the active material in each active layer is less than or equal to 15 μm.
[0082] Optionally, the volume distribution particle size Dv50 of the active material in each active layer is independently selected from 100 nm to 15 μm.
[0083] In the above “100nm~15μm”, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and the following point values: 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 800nm, 850nm, 900nm, 950nm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm; or a range consisting of any two values, for example: 100nm~15μm, 200nm~15μm, 300nm~15μm, 400nm~15μm, 500nm~15μm, 600nm~15μm, 700nm~15μm, 800nm~15μm, 900nm~15μm, 1μm~15μm, 3μm~15μm, 4μm~15μm m, 5μm~15μm, 6μm~15μm, 8μm~15μm, 10μm~15μm, 100nm~10μm, 200nm~10μm, 300nm~10μm, 400nm~10μm, 500nm~10μm, 600 nm~10μm, 700nm~10μm, 800nm~10μm, 900nm~10μm, 1μm~10μm, 3μm~10μm, 4μm~10μm, 5μm~10μm, 7μm~10μm, 8μm~10μm, 10 0nm~5μm,200nm~5μm,300nm~5μm,400nm~5μm,500nm~5μm,600nm~5μm,700nm~5μm,800nm~5μm,900nm~5μm,1μm~5μm,1 00nm~3μm, 200nm~3μm, 300nm~3μm, 400nm~3μm, 500nm~3μm, 600nm~3μm, 700nm~3μm, 800nm~3μm, 900nm~3μm, 1μm~3μm.
[0084] In some of the embodiments, the volume distribution particle size Dv50 of the active material in each active layer is independently selected from 100 nm to 10 μm.
[0085] In some embodiments, the absolute value of the difference in volume distribution particle size Dv50 of the active material in any two adjacent active layers is K, and K≤12 μm.
[0086] In some embodiments, the absolute value of the difference in volume distribution particle size Dv50 of the active material in any two adjacent active layers is K, and K≤10 μm.
[0087] In some of the embodiments, the absolute value of the difference in volume distribution particle size Dv50 of the active material in any two adjacent active layers is K, and 0.5 μm≤K≤12 μm.
[0088] Optionally, 0.5 μm ≤ K ≤ 10 μm.
[0089] Optionally, 0.5 μm≤K≤5 μm.
[0090] The difference in volume distribution particle size of the active materials in two adjacent active layers is further regulated, so that the larger particles of active materials and the smaller particles of active materials can further play a better synergistic compounding role.
[0091] In the above “0.5μm≤K≤12μm”, the value of K includes the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiment and the following point values: 0.5μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm; or a range consisting of any two values, for example: 0.5μm~10μm, 1μm~10μm, 2μm~10μm, 3μm~10μm, 4μm~10μm, 5μm~10μm, 6μm~10μm, 7μm~10μm, 8μm~10μm, 0.5μm~9μm, 1μm~10μm m~9μm, 2μm~9μm, 3μm~9μm, 4μm~9μm, 5μm~9μm, 6μm~9μm, 7μm~9μm, 8μm~9μm , 0.5μm~8μm, 1μm~8μm, 2μm~8μm, 3μm~8μm, 4μm~8μm, 5μm~8μm, 6μm~8μm, 7μm ~8μm, 0.5μm~6μm, 1μm~6μm, 2μm~6μm, 3μm~6μm, 4μm~6μm, 5μm~6μm, 0.5μm~ 5μm, 1μm~5μm, 2μm~5μm, 3μm~5μm, 4μm~5μm, 0.5μm~3μm, 1μm~3μm, 2μm~3μm.
[0092] In some of the embodiments, in each active layer, the proportion of active material is independently selected from: 70 wt % to 99 wt %.
[0093] Optionally, in each active layer, the proportion of active material is independently selected from: 80 wt % to 95 wt %.
[0094] In some of the embodiments, in each active layer, the proportion of the solid electrolyte is independently selected from: 0.1 wt % to 30 wt %.
[0095] In some of the embodiments, in each active layer, the proportion of the solid electrolyte is independently selected from: 0.1 wt % to 20 wt %.
[0096] In some of the embodiments, in each active layer, the proportion of the solid electrolyte is independently selected from: 0.1 wt % to 15 wt %.
[0097] The active material in the present application can be any of the active materials commonly used in various types of battery pole pieces in the art, including any of the positive electrode materials and negative electrode materials. It can be understood that when the active material is a positive electrode active material, the battery pole piece is a positive electrode piece. Similarly, when the active material is a negative electrode active material, the battery pole piece is a negative electrode piece. The following are examples of commonly used positive electrode materials and negative electrode materials, but are not limited to the following.
[0098] The positive electrode active material may be any positive electrode active material commonly used in the art, including but not limited to: positive electrode active materials for lithium ion batteries, positive electrode active materials for sodium ion batteries, and positive electrode active materials for potassium ion batteries.
[0099] The positive electrode active material of a lithium ion battery, the positive electrode active material of a sodium ion battery and the positive electrode active material of a potassium ion battery are hereinafter referred to as lithium ion active material, sodium ion active material and potassium ion active material, respectively.
[0100] Further, as an example, the lithium ion active material may include at least one of the following materials: lithium phosphates containing olivine structure, lithium transition metal oxides and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries can also be used. These positive electrode active materials can be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM211), LiNi0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (referred to as NCM811), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.1 Al 0.05 O2) and its modified compounds. Examples of lithium-containing phosphates with olivine structure may include but are not limited to at least one of lithium iron phosphate (such as LiFePO4, referred to as LFP), lithium manganese phosphate (such as LiMnPO4), and lithium manganese iron phosphate. In any embodiment of the present application, the molecular formula of the lithium ion active material is: LiFe x Mn (1-x) PO4, x can be any number from 0 to 1.
[0101] It can be understood that when x is 0, LiFe x Mn (1-x) PO4 is LiMnPO4 lithium manganese phosphate. When x is 1, LiFePO4 is LiFePO4 lithium iron phosphate (LFP).
[0102] It should be noted that the lithium content in the positive electrode material exemplified above refers to its content when it is not in use. During the use of the battery, it will be repeatedly used as a battery, and the Li in the positive electrode active material will change during the charging and discharging process, that is, the molar subscript of Li in the positive electrode active material in the battery product will not always remain at 1, but will change; further, the range of change can be (0 to 1.2).
[0103] For example, LiFe x Mn (1-x) PO4 can be further expressed as Li y Fe x Mn (1-x) PO4, y is 0~1.1.
[0104] For example, for the ternary material Li y (Ni a Co b Mn c ) 1-d M d O 2-x A x , y is 0.2~1.2, a+b+c=1, 0≤d≤1, 0≤x<2; M is one or more of Zr, Sr, B, Ti, Mg, Sn and Al, and A is one or more of S, N, F, Cl, Br and I.
[0105] The battery will be accompanied by Li deintercalation and consumption during the charge and discharge process. The molar content of Li is different when the battery is discharged to different states. The above definition of y includes the molar content of Li under different charge and discharge states of the battery; further, the battery voltage is usually between 2-5V.
[0106] As an example, the sodium ion active material may include at least one of the following materials: at least one of a sodium transition metal oxide, a polyanionic compound, and a Prussian blue compound. However, the present application is not limited to these materials, and other conventionally known materials that can be used as positive electrode active materials for sodium ion batteries may also be used.
[0107] As an optional technical solution of the present application, in the sodium transition metal oxide, the transition metal includes at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. The sodium transition metal oxide is, for example, Na x MO2, wherein M includes at least one or more of Ti, V, Mn, Co, Ni, Fe, Cr and Cu, and 0<x≤1.
[0108] As an optional technical solution of the present application, the polyanionic compound can be a compound having sodium ions, transition metal ions and tetrahedral (YO4) n- A class of compounds with anionic units. Transition metals include at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; Y includes at least one of P, S and Si; n represents (YO4) n- valence state.
[0109] Polyanionic compounds can also be those with sodium ions, transition metal ions, tetrahedral (YO4) n- A class of compounds containing anion units and halogen anions. The transition metal includes at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; Y includes at least one of P, S and Si, and n represents (YO4) n- valence state; the halogen may be at least one of F, Cl and Br.
[0110] Polyanionic compounds can also be sodium ions, tetrahedral (YO4) n- Anion unit, polyhedral unit (ZO y ) m+ and a class of compounds containing an optional halogen anion. Y includes at least one of P, S and Si, and n represents (YO4) n- valence state; Z represents a transition metal, including at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; m represents (ZOy ) m+ valence state; the halogen may be at least one of F, Cl and Br.
[0111] Polyanionic compounds include NaFePO4, Na3V2(PO4)3 (sodium vanadium phosphate, abbreviated as NVP), Na4Fe3(PO4)2(P2O7)(NFPP), NaM1PO4F and Na3(VO y )2(PO4)2F (3-2y) At least one of .
[0112] M1 is at least one of V, Fe, Mn and Ni, and 0≤y≤1.
[0113] Prussian blue compounds can be sodium ions, transition metal ions and cyanide ions (CN - ). The transition metal includes at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. Prussian blue compounds are, for example, Na a M2 b M3 c (CN)6, wherein M2 and M3 are each independently selected from at least one of Ni, Cu, Fe, Mn, Co and Zn, 0<a≤2, 0<b<1, 0<c<1.
[0114] In some of the embodiments, the battery electrode is a negative electrode, and the active material is a negative electrode active material; further, it includes at least one of a silicon-based active material and a carbon-based active material.
[0115] The above-mentioned negative electrode active materials include mesophase carbon microspheres, graphite, glassy carbon, carbon nanotubes, carbon-carbon composites, carbon fibers, hard carbon, soft carbon, silicon-based materials, tin-based materials, magnesium-based materials, iron-based materials, metallic lithium, lithium metal and alloys formed by other metals or non-metallic elements; further, other metals include at least one of tin (Sn), zinc (Zn), aluminum (Al), magnesium (Mg), silver (Ag), gold (Au), gallium (Ga), indium (In) and platinum foil (Pt); non-metallic elements include at least one of boron (B), carbon (C) and silicon (Si).
[0116] Optionally, specific examples of the above-mentioned negative electrode active materials include, but are not limited to: at least one of mesophase carbon microbeads, natural graphite, artificial graphite, graphene, glassy carbon, carbon nanotubes, carbon fibers, hard carbon, soft carbon, iron oxide, tin oxide, silicon oxide, magnesium oxide, silicon-carbon composites, lithium metal and lithium metal alloys.
[0117] In some embodiments, the surface capacity of each active layer is independently selected from: 1 mAh / cm 2~3 mAh / cm 2 。
[0118] In the present application, the solid electrolyte may be a solid electrolyte commonly used in the art, such as various lithium-ion solid electrolytes, sodium-ion solid electrolytes, and potassium-ion solid electrolytes commonly used in the art.
[0119] In some of the embodiments, the solid electrolyte substrate is a lithium-ion solid electrolyte.
[0120] Here, the lithium-ion solid electrolyte is exemplified, including but not limited to at least one of oxide solid electrolytes, sulfide electrolytes, and halide electrolytes.
[0121] Oxide solid electrolytes: LISICON type: such as γ-Li3PO4, etc.; NASICON type; such as Li (1+x1) Q x M (2-x1) (PO4)3, 0 ≤ x1 < 1, Q includes at least one of Al, Cr, Ba, Fe, Sc, In, Lu, Y, La; M includes at least one of G, Ti; Garnet type; such as Li (7-x2) La3Zr (2-x2) M x2 O 12 etc., 0 ≤ x2 < 1, M includes at least one of Sb, Nb, Ta, Te, W; LIPON type: such as Li x3 PO y1 N z1 ; 0 < x3 ≤ 1, 0 < y1 ≤ 1, 0 < z1 ≤ 1; Perovskite type: such as Li3 x 4Q (2 / 3-x4) MO3, etc., 0.04 < x4 < 0.17, Q includes at least one of La, Sr, Ba, Nd, M includes at least one of Al, Ti, Ge; Anti-Perovskite type: such as Li3OCl, etc.; Thio-LiSICON type: such as Li (3+x5) My2A (1-y2) Q (4-z2) T z2 , where -1 < x5 < 2, 0 ≤ y2 ≤ 1, 0 ≤ z2 ≤ 2, M includes at least one of B, Al, In, Si, Ge, Sn, Ti, W, Mo, A includes at least one of P, As, Sb, Bi, Q includes at least one of S, Se, T includes at least one of F, Cl, Br, I;
[0122] Sulfide solid electrolytes, including: Thiophosphate type: Li3PS4, etc., Argyrodite type: Li6PS5Cl, Li5.5 PS 5.5 Cl 1.5 , Halide type: Li3InCl6, Hydride type: 0.7Li(CB9H 10 ) - 0.3Li(CB 11 H 12 ) or at least one of; for example, Li (10+x6) M (1+y3) A (2-y3) Q (12-z3) H z3 type: where -2 < x6 < 2, 0 ≤ y3 ≤ 2, 0 ≤ z3 ≤ 2, M includes at least one of B, Al, In, Si, Ge, Sn, Ti, W, Mo; A includes at least one of P, As, Sb, Bi, Q includes at least one of S, Se, H includes at least one of F, Cl, Br, I: (100 - x7)Li2S·x7M·y4Q type: where 20 ≤ x7 ≤ 30, 0 ≤ y4 ≤ 50, M includes at least one of B2S3, Al2S3, In2S3, SiS2, GeS2, SnS2, P2S5, As2S3, Sb2S5, Bi2S3, WS2, MoS2, Q includes at least one of B2O3, Al2O3, In2O3, SiO2, GeO2, SnO2, P2O5, Sb2O5, Bi2O3, WO2, WO3, MoO2, MoO3, Fe2O3, ZnO, MgO, CuO, CaO, LiN, Li2O, LiF, LiCl, LiBr, LiI; Argyrodite type: Li (6+x8) M y5 A (1-y5) Q (5-z5) T (1+z5) , where -1 ≤ x8 ≤ 1, 0 ≤ y5 ≤ 1, -1 < z5 ≤ 1, M includes at least one of B, Al, In, Si, Ge, Sn, Ti, W, Mo, A includes at least one of P, As, Sb, Bi, Q includes at least one of S, Se, T includes at least one of F, Cl, Br, I; Halide type: Li3MJ or Li2Sc 2 / 3 J; M includes at least one of Y, Er, In, Sc, Ga, J includes at least one of F, Cl, Br, I.
[0123] When the above sulfide solid electrolyte is a sulfide - type solid electrolyte, it includes but is not limited to: argyrodite electrolyte; binary sulfide - type solid systems such as Li2S - P2S5, Li2S - SiS2, Li2S - GeS, and Li2S - B2S3, Li2S - Me - P2S5 ternary systems, where Me includes Si, Ge, Sn, or Al, etc.
[0124] Specifically, the above-mentioned sulfide electrolyte includes at least one of Li2S-P2S5, Li2S-SiS2, Li2S-GeS, Li2S-B2S3, and Li2S-Me-P2S5.
[0125] The halide electrolytes include, but are not limited to: Li3InCl6, Li3YCl6, Li3ScCl6, Li3ErCl6, Li2ZrCl6, etc.
[0126] The sodium solid-state electrolytes include, but are not limited to: NASICON type: Na (1+x9+2y5) Zr (2-y5) M y5 P (3-x9) Si x9 O 12 , 0 ≤ x9 ≤ 3, 0 ≤ y5 ≤ 1, M includes at least one of Zn, Mg, Ca; Na-β-Alumina type: Na2O·2Al2O3 or Na2O·3Al2O3, etc.; Na (3+x10) M y6 A (1-y6) Q (4-z6) T z6 type, where -1 < x10 < 2, 0 ≤ y6 ≤ 1, 0 ≤ z6 ≤ 2, M includes at least one of B, Al, In, Si, Ge, Sn, Ti, W, Mo, A includes at least one of P, As, Sb, Bi, Q includes at least one of S, Se, and T includes at least one of F, Cl, Br, I; Na (11+x11) M (2-y7) A (1+y7) Q (12-z7) T z7 type where -1 < x11 < 1, 0 ≤ y7 ≤ 2, 0 ≤ z7 ≤ 2, M includes at least one of B, Al, In, Si, Ge, Sn, Ti, W, Mo, A includes P, As, Sb, Bi; Q = at least one of S, Se, and T includes at least one of F, Cl, Br, I; Anti-perovskite type Na3OX, X includes at least one of Cl, Br, I, BH4.
[0127] The potassium solid-state electrolytes include, but are not limited to: β-Alumina type such as K2O x13 Al2O3, etc., x13 takes any number from 8 to 11, Anti-Perovskite type such as K3OI, etc., and at least one of K2Fe4O7 type and KSi2P3 type.
[0128] In some of these embodiments, the total areal capacity of the n-layer active layer is not less than 4 mAh / cm 2 .
[0129] In some embodiments, the total surface capacity of the n-layer active layer is 4 mAh / cm 2 ~8mAh / cm 2 .
[0130] In some embodiments, the thickness of each active layer is independently selected from 20 μm to 60 μm.
[0131] In some embodiments, the total thickness of the n-active layer is 80 μm to 300 μm.
[0132] In some embodiments, n may be 2, 3, 4, 5, 6, 7, 8, 9 or 10.
[0133] In some embodiments, n is an integer greater than or equal to 3.
[0134] In some of the embodiments, the composition of each active layer further includes a conductive agent.
[0135] Optionally, in each active layer, the mass proportion of the conductive agent is independently selected from 0.1wt% to 5wt%;
[0136] In some of the embodiments, the composition of each active layer further includes a binder.
[0137] Optionally, in each active layer, the mass proportion of the binder is independently selected from 0.1 wt % to 5 wt %.
[0138] The conductive agent may be a conductive material commonly used in the art, including but not limited to at least one of graphite, carbon nanotubes, nanofibers, carbon black and graphene. Specifically, it may include at least one of conductive carbon black (super pll, referred to as SP), conductive graphite SFG-6, conductive graphite KS-6, acetylene black, superconducting carbon black Ketjen black (ECP) with a branched structure, vapor grown carbon fiber (VGCF), carbon nanotubes (CNTs) and graphene and composite conductive agents thereof.
[0139] The above-mentioned binder can adopt the binder commonly used in the art, which may include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, hydrogenated nitrile rubber, styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), carboxymethyl chitosan (CMCS) and at least one of fluorine-containing acrylate resins.
[0140] The positive electrode sheet can be prepared by a commonly used preparation method in the art, for example, by the following steps:
[0141] N active material layers are sequentially formed on the same surface of at least one side of the current collector.
[0142] Alternatively, the method of forming the active material layer may adopt any one of wet film formation and dry film formation.
[0143] Specifically, the wet film formation is to mix the components of the active material layer in a solvent to form an active slurry, then coat the active slurry on the surface of the current collector, and dry it to obtain the active material layer.
[0144] Specifically, the dry film forming method is to directly mix and press the components of the above-mentioned active material layer into an active material layer, and then composite and press the active material layer with a current collector to prepare a positive electrode sheet.
[0145] An embodiment of the present application further provides a battery, the battery comprising the above-mentioned battery electrode.
[0146] It can be understood that the above-mentioned battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. At least one of the positive electrode sheet and the negative electrode sheet adopts the above-mentioned battery electrode sheet.
[0147] In some of the embodiments, the battery electrode is a positive electrode, and the battery is a solid-state battery, then the battery also includes a negative electrode and an electrolyte. The following takes the all-solid-state electrolyte system as an example to illustrate the negative electrode and the electrolyte, including but not limited to the following.
[0148] In some of the embodiments, the electrolyte is a solid electrolyte; further, the electrolyte exists in the form of an electrolyte membrane, which is located between the positive electrode sheet and the negative electrode sheet.
[0149] The type of solid electrolyte can be selected as described above and will not be repeated here.
[0150] The negative electrode sheet can be a negative electrode sheet used in various systems in the art.
[0151] In some embodiments, the negative electrode sheet includes a current collector and a negative electrode active layer supported on a surface of the current collector.
[0152] The components of the negative electrode active layer include a negative electrode active material.
[0153] The negative electrode active material mentioned above can adopt the commonly used negative electrode active materials in this application.
[0154] In any embodiment of the present application, the above-mentioned negative electrode active material includes mesophase carbon microbeads, graphite, glassy carbon, carbon nanotubes, carbon-carbon composite materials, carbon fibers, hard carbon, soft carbon, silicon-based materials, tin-based materials, magnesium-based materials, iron-based materials, metallic lithium, lithium metal and other metal or non-metallic elements; further, other metals include tin (Sn), zinc (Zn), aluminum (Al), magnesium (Mg), silver (Ag), gold (Au), gallium (Ga), indium (In) and platinum (Pt) at least one; non-metallic elements include boron (B), carbon (C) and silicon (Si) at least one.
[0155] Optionally, specific examples of the above-mentioned negative electrode active materials include, but are not limited to: at least one of mesophase carbon microbeads, natural graphite, artificial graphite, graphene, glassy carbon, carbon nanotubes, carbon fibers, hard carbon, soft carbon, iron oxide, tin oxide, silicon oxide, magnesium oxide, silicon-carbon composites, lithium metal and lithium metal alloys.
[0156] In any embodiment of the present application, the battery is a lithium battery, and the mass proportion of the negative electrode active material in the negative electrode active layer is 70% to 100%.
[0157] In any embodiment of the present application, the components of the negative electrode active layer further include a negative electrode conductive agent and a negative electrode binder.
[0158] In any embodiment of the present application, the above-mentioned negative electrode conductive agent can be a conductive material commonly used in the art, including but not limited to: at least one of graphite, carbon nanotubes, nanofibers, carbon black and graphene. Specifically, it can include at least one of conductive carbon black (super pll, referred to as SP), conductive graphite SFG-6, conductive graphite KS-6, acetylene black, superconducting carbon black Ketjen black (ECP) with a branched structure, vapor-grown carbon fiber (VGCF), carbon nanotubes (CNTs) and graphene and composite conductive agents thereof.
[0159] The weight ratio of the negative electrode conductive agent in the negative electrode active layer is 0 to 20 wt % based on the total weight of the negative electrode active layer.
[0160] The above-mentioned negative electrode binder can adopt the binder commonly used in the art, and may include at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0161] The weight ratio of the negative electrode binder in the negative electrode active layer is 0 to 30 wt % based on the total weight of the negative electrode active layer.
[0162] In any embodiment of the present application, the negative electrode active layer may further include other additives, such as thickeners, such as sodium carboxymethyl cellulose (CMC-Na), etc. Based on the total weight of the negative electrode active layer, the weight ratio of other additives in the negative electrode active layer is 0-15wt%.
[0163] In any embodiment of the present application, the current collector in the negative electrode sheet may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil.
[0164] The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be formed by forming a metal material on a polymer material substrate.
[0165] In some embodiments, the metal material includes at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy.
[0166] In some of the embodiments, the polymer material substrate includes at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0167] In any embodiment of the present application, the negative electrode sheet can be prepared in the following manner: the above-mentioned components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained. The solid content of the negative electrode slurry is 30wt% to 70wt%, and the viscosity at room temperature is adjusted to 2000mPa·s to 10000mPa·s; the obtained negative electrode slurry is coated on the negative electrode current collector, and after a drying process, cold pressing such as a roller, a negative electrode sheet is obtained.
[0168] In some embodiments, the surface density of the negative electrode active material contained in the negative electrode sheet is 0.005 g / cm 2 ~0.03g / cm 2 .
[0169] The surface density of the negative electrode active material = the mass of the negative electrode active material / the area of the negative electrode sheet.
[0170] In other embodiments, the negative electrode may directly adopt a lithium-containing metal film.
[0171] In some of the embodiments, the component of the lithium-containing metal membrane may be metallic lithium, or may be an alloy formed by metallic lithium and other metallic elements or non-metallic elements.
[0172] In some of the embodiments, the other metal elements include at least one of tin (Sn), zinc (Zn), aluminum (Al), magnesium (Mg), silver (Ag), gold (Au), gallium (Ga), indium (In), and platinum (Pt).
[0173] In some of the embodiments, the non-metallic element includes at least one of boron (B), carbon (C) and silicon (Si).
[0174] In some embodiments, the battery further comprises a separator, which is disposed between the positive electrode sheet and the negative electrode sheet.
[0175] It should be noted that if the above-mentioned battery is an all-solid-state battery, an isolation film may not be provided.
[0176] The present application has no particular limitation on the type of isolation membrane, and any known porous isolation membrane with good chemical stability and mechanical stability can be selected.
[0177] In some embodiments, the material of the isolation membrane may include at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.
[0178] The shape of the battery of the present application is not particularly limited, and it can be cylindrical, square or any other shape, for example Figure 1 The battery cell 4 is a battery having a square structure as an example.
[0179] In some embodiments, the battery may include a housing for encapsulating a positive electrode sheet, a negative electrode sheet, and an electrolyte membrane.
[0180] In some embodiments, reference Figure 2 The housing may include a shell 41 and a cover plate 43. The shell 41 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 41 has an opening connected to the receiving cavity, and the cover plate 43 can be covered on the opening to close the receiving cavity.
[0181] The positive electrode sheet, the negative electrode sheet and the electrolyte membrane are assembled to form an electrode assembly 42. The electrode assembly 42 is encapsulated in the receiving cavity. The number of electrode assemblies 42 contained in the battery cell 4 can be one or more, which can be adjusted according to demand.
[0182] In some embodiments, the outer shell can be a soft bag, and the material can be plastic, such as one or more of polypropylene PP, polybutylene terephthalate PBT, polybutylene succinate PBS, etc.; the outer shell can also be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc.
[0183] In some of these embodiments, the battery includes one or more battery cells 4 .
[0184] In some embodiments, the battery may be a battery module or a battery pack; the battery module or battery pack includes at least one battery cell. The number of battery cells contained in the battery module may be one or more, and those skilled in the art may select a suitable number according to the application and capacity of the battery module.
[0185] Figure 3 and Figure 4 The battery pack 1 is used as an example. The battery pack 1 includes a battery box and one or more battery cells 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for the battery cells 4.
[0186] The plurality of battery cells 4 may be arranged in the battery box in any manner.
[0187] The present application also provides an electrical device, which includes the above-mentioned battery.
[0188] Furthermore, in the above-mentioned electrical device, the battery may exist in the form of a battery cell, or may be further assembled into a battery pack.
[0189] The above-mentioned battery or the battery pack assembled therefrom can be used as a power source for an electrical device, and can also be used as an energy storage unit for an electrical device.
[0190] The above-mentioned electrical devices may be, but are not limited to, mobile equipment, electric vehicles, electric trains, ships and satellites, energy storage systems, etc.
[0191] Mobile devices include but are not limited to: mobile phones, laptops, etc. Electric vehicles include but are not limited to: pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.
[0192] Figure 5 The power consumption device 5 is taken as an example. The power consumption device 5 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the power consumption device 5's requirements for high power and high energy density of the battery, a battery pack can be used.
[0193] As another example, the power-consuming device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a battery may be used as a power source.
[0194] The present application will be described below in conjunction with specific embodiments, but the present application is not limited to the following embodiments. It should be understood that the attached claims summarize the scope of the present application. Under the guidance of the concept of the present application, technical personnel in the field should realize that certain changes made to the various embodiments of the present application will be covered by the spirit and scope of the claims of the present application.
[0195] The following are specific embodiments.
[0196] Example 1
[0197] (1) Preparation of positive electrode
[0198] S1: LiNi positive electrode active material with Dv50 of 4μm 0.83 Co 0.12 Mn 0.05 O2, sulfide solid electrolyte Li6PS5Cl with a Dv50 of 1 μm, conductive agent vapor-grown carbon fiber (hereinafter referred to as VGCF) and binder polytetrafluoroethylene (hereinafter referred to as PTFE) are weighed in a mass ratio of 85:13:1:1, mixed evenly in a double planetary mixer, and then the evenly mixed powder is heated and pressurized in an internal mixer to knead into a mass material, and then hot roller pressed at 80°C into a first positive electrode active layer with a thickness of 50 μm.
[0199] S2: LiNi positive electrode active material with Dv50 of 8μm 0.83 Co 0.12 Mn 0.05 O2, sulfide electrolyte Li6PS5Cl with a Dv50 of 1 μm, conductive agent VGCF and binder PTFE were weighed in a mass ratio of 85:13:1:1, mixed evenly in a double planetary mixer, and then the evenly mixed powder was heated and pressurized in an internal mixer to knead into a mass material, and then hot roller pressed at 80°C to form a second positive electrode active layer with a thickness of 50 μm.
[0200] Among them, the surface capacity of the first active layer is 2.5 mAh / cm 2 The surface capacity of the second active layer is 2.5 mAh / cm 2 The total surface capacity of the positive electrode is 5 mAh / cm 2 .
[0201] S3: The first positive electrode active layer is firstly hot-rolled composited with a current collector Al foil having a thickness of 12 μm, and then the second positive electrode active layer is hot-rolled composited on the surface of the first positive electrode active layer to obtain a positive electrode sheet.
[0202] The structural diagram of the positive electrode sheet 421 is as follows Figure 6As shown, a first positive electrode active layer 421b and a second positive electrode active layer 421c are sequentially stacked on one side surface of the current collector 421a, and the components in the first positive electrode active layer 421b and the second positive electrode active layer 421c both contain positive electrode active material 4211, and the Dv50 of the positive electrode active material 4211 in the first positive electrode active layer 421b is less than the Dv50 of the positive electrode active material 4211 in the second positive electrode active layer 421c.
[0203] The above-mentioned Dv50 is the particle size corresponding to 50% volume distribution in the particle size-volume cumulative distribution curve, which can be obtained based on the volume cumulative distribution curve. As an example, it can be carried out with reference to the relevant standards of GB / T19077-2016 / ISO 13320:2009, and can be conveniently measured using a laser particle size analyzer, such as the Mastersizer 2000E laser particle size analyzer of Malvern Instruments Ltd. in the United Kingdom.
[0204] Refer to GB / T19077-2016 / ISO 13320:2009 standard process, the specific test process is as follows:
[0205] Take an appropriate amount of the sample to be tested and add it to deionized water. The sample concentration should be 8% to 12% shading. Ultrasonicate for 5 minutes to ensure that the sample is completely dispersed. Then measure the sample according to GB / T19077-2016 / ISO13320:2009 standard.
[0206] (2) Preparation of all-solid-state batteries
[0207] 100 mg of sulfide electrolyte LPSCl was weighed and added to the battery mold, and pressurized to obtain an electrolyte membrane with a thickness of 800 μm. The electrolyte membrane was then placed on one side of the positive electrode sheet where the second positive electrode active layer was located, and a 150 μm thick InLi alloy sheet was placed on the other side as the negative electrode sheet to assemble into an all-solid-state battery.
[0208] (3) Performance test:
[0209] S1, first discharge capacity
[0210] The specific process is as follows: at 25±3°C, the assembled all-solid-state battery is charged to 3.68V (4.3V for lithium potential) at a current density of 0.1C, left to stand for 10 minutes, and then discharged to 2.18V (2.8V for lithium potential) at a current density of 0.1C to obtain the battery's first discharge capacity, recorded as the first discharge 0.1C.
[0211] Where 1C = 200mA / g.
[0212] S2, rate performance
[0213] The specific process is as follows: at 25±3℃, the charging rate of the all-solid-state battery is fixed at 0.1C, and then discharged at rates of 0.33C, 1C, 2C, and 3C, and the cycle test is 3 cycles at each rate; the voltage test window is 2.8~4.3V vs.Li + / Li, where 1C = 200mA / g.
[0214] S3, Cycle performance:
[0215] The specific process is as follows: At 25±3℃, the assembled all-solid-state battery is first charged and discharged at 0.1C for 3 cycles, and the battery voltage test window is 2.8~4.3V vs.Li + / Li, obtain the initial capacity, and then continue to charge and discharge at 0.33C for cyclic charge and discharge test to obtain the capacity after 200 cycles of cyclic charge and discharge. The percentage of the capacity after 200 cycles of cyclic charge and discharge to the initial capacity is the cycle capacity retention rate P200, where 1C = 200mA / g.
[0216] The test results are shown in Table 1.
[0217] Embodiments 2 to 11
[0218] Examples 2 to 11 are basically the same as Example 1, except that in step (1) of preparing the positive electrode sheet, the particle size Dv50 of the positive electrode active material or the particle size Dv50 of the solid electrolyte used in the first positive electrode active layer or the second positive electrode active layer is regulated.
[0219] The other step conditions are the same as those in Example 1. The test results are shown in Table 1.
[0220] Example 12
[0221] Example 12 is basically the same as Example 1, except that the steps for preparing the positive electrode sheet are as follows:
[0222] S1: LiNi positive electrode active material with Dv50 of 4μm 0.83 Co 0.12 Mn 0.05 O2, sulfide solid electrolyte Li6PS5Cl with a Dv50 of 1 μm, conductive agent VGCF and binder PTFE are weighed in a mass ratio of 85:13:1:1, mixed evenly in a double planetary mixer, and then the evenly mixed powder is heated and pressurized in an internal mixer to knead into a mass material, and then hot roller pressed at 80°C to form the first positive electrode active layer.
[0223] S2: LiNi positive electrode active material with Dv50 of 6μm 0.83 Co 0.12 Mn 0.05O2, sulfide electrolyte Li6PS5Cl with a Dv50 of 1 μm, conductive agent VGCF and binder PTFE were weighed in a mass ratio of 85:13:1:1, mixed evenly in a double planetary mixer, and then the evenly mixed powder was heated and pressurized in an internal mixer to knead into a mass material, and then hot roller pressed at 80°C to form a second positive electrode active layer.
[0224] S3: LiNi positive electrode active material with Dv50 of 8μm 0.83 Co 0.12 Mn 0.05 O2, sulfide solid electrolyte Li6PS5Cl with a Dv50 of 1 μm, conductive agent VGCF and binder PTFE are weighed in a mass ratio of 85:13:1:1, mixed evenly in a double planetary mixer, and then the evenly mixed powder is heated and pressurized in an internal mixer to knead into a mass material, and then hot roller pressed at 80°C to form the first positive electrode active layer.
[0225] S4: The first positive electrode active layer is firstly hot-rolled with the current collector Al foil, and then the second positive electrode active layer is hot-rolled on the surface of the first positive electrode active layer, and then the third positive electrode active layer is hot-rolled on the surface of the second positive electrode active layer to obtain a positive electrode sheet.
[0226] The first positive electrode active layer, the second positive electrode active layer and the third positive electrode active layer have the same thickness, and the total thickness is 100 μm.
[0227] The other step conditions are the same as those in Example 1. The test results are shown in Table 1.
[0228] Example 13
[0229] Example 13 is basically the same as Example 1, except that in step (1), the positive electrode active materials in the first positive electrode active layer and the second positive electrode active layer are replaced with LiNi 0.9 Co 0.5 Mn 0.5 O2, for specific parameters, see Table 1.
[0230] The other step conditions are the same as those in Example 1. The test results are shown in Table 1.
[0231] Comparative Example 1
[0232] Comparative Example 1 is substantially the same as Example 1, except that in step (1) of preparing the positive electrode sheet, the first positive electrode active layer having a thickness of 100 μm is directly composited with the current collector Al foil by hot rolling to prepare the positive electrode sheet.
[0233] The other step conditions are the same as those in Example 1. The test results are shown in Table 1.
[0234] Comparative Example 2
[0235] Comparative Example 2 is basically the same as Example 1, except that in step (1) of preparing the positive electrode sheet, the particle size Dv50 of the positive electrode active material used in the first positive electrode active layer and the second positive electrode active layer is regulated differently from that in Example 1.
[0236] The other step conditions are the same as those in Example 1. The test results are shown in Table 1.
[0237] The relevant parameters and performance test results of each embodiment and comparative example are shown in Table 1. Wherein, K is the absolute value of the difference between the volume distribution particle size Dv50 of the positive electrode active material in the second positive electrode active layer and the volume distribution particle size Dv50 of the positive electrode active material in the first positive electrode active layer.
[0238] Table 1
[0239]
[0240]
[0241] “ / ” indicates that the structural substance or parameter does not exist.
[0242] By analyzing the data in Table 1 and comparing the data in Examples 1 to 13 and Comparative Examples 1 to 2, it can be seen that in the present application, by adjusting the particle size of the active material in the active layer at different distances from the current collector in the battery electrode, the active material with a larger particle size and the active material with a smaller particle size can work synergistically, thereby improving the rate performance and cycle performance of the battery.
[0243] And it can be seen from the data in Table 1 that even in a high capacity system, that is, a high energy density system, it can still have a high first discharge capacity, excellent rate performance and good cycle performance.
[0244] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0245] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims, and the description and drawings may be used to interpret the contents of the claims.
Claims
1. A battery pole piece, characterized in that: The battery pole piece comprises a current collector and n active layers sequentially arranged on at least one side of the current collector; components of each active layer include active materials and solid electrolytes; In any two adjacent active layers, the volume distribution particle size Dv50 of the active material in the active layer closer to the current collector is smaller than the volume distribution particle size Dv50 of the active material in the other active layer; n is an integer greater than or equal to 2.
2. The battery pole piece according to claim 1, characterized in that: In at least one of the active layers, the volume distribution particle size Dv50 of the active material is greater than the volume distribution particle size Dv50 of the solid electrolyte; Optionally, in each active layer, the volume distribution particle size Dv50 of the active material is greater than the volume distribution particle size Dv50 of the solid electrolyte.
3. The battery electrode according to any one of claims 1 to 2, characterized in that: The volume distribution particle size Dv50 of the solid electrolyte in each active layer is less than or equal to 10 μm; Optionally, the volume distribution particle size Dv50 of the solid electrolyte in each active layer is independently selected from 50 nm to 10 μm; Further optionally, the volume distribution particle size Dv50 of the solid electrolyte in each active layer is independently selected from 50 nm to 5 μm.
4. The battery electrode according to any one of claims 1 to 3, characterized in that: The volume distribution particle size Dv50 of the active material in each active layer is less than or equal to 15 μm; Optionally, the volume distribution particle size Dv50 of the active material in each active layer is independently selected from 100 nm to 15 μm; Further optionally, the volume distribution particle size Dv50 of the active material in each active layer is independently selected from 100 nm to 10 μm.
5. The battery electrode according to any one of claims 1 to 3, characterized in that: The absolute value of the difference in volume distribution particle size Dv50 of the active material in any two adjacent active layers is K, K≤12 μm; Optionally, 0.5 μm ≤ K ≤ 12 μm; Further optionally, 0.5 μm≤K≤5 μm.
6. The battery electrode according to any one of claims 1 to 3, characterized in that: The battery electrode satisfies any one of the following conditions (1) to (2): (1) In each active layer, the proportion of the active material is independently selected from: 70wt% to 99wt%; Optionally, in each active layer, the proportion of the active material is independently selected from: 80wt% to 95wt%; (2) In each active layer, the proportion of the solid electrolyte is independently selected from: 0.1wt% to 30wt%.
7. The battery electrode according to any one of claims 1 to 3, characterized in that: The active layer satisfies at least one of the following conditions (3) to (4): (3) The surface capacity of each active layer is independently selected from: 1 mAh / cm 2 ~3mAh / cm 2 ; (4) The total surface capacity of the n-layer active layer is not less than 4 mAh / cm 2 ; Optionally, the total surface capacity of the n-layer active layer is 4 mAh / cm 2 ~8mAh / cm 2 .
8. The battery electrode according to any one of claims 1 to 3, characterized in that: The active layer satisfies at least one of the following conditions (5) to (6): (5) The thickness of each active layer is independently selected from 20 μm to 60 μm; (6) The total thickness of the n-layer active layer is 80 μm to 300 μm.
9. The battery electrode according to any one of claims 1 to 3, characterized in that: The active layer satisfies at least one of the following conditions (7) to (8): (7) The active material includes a positive electrode active material; (8) The solid electrolyte includes at least one of an oxide solid electrolyte, a sulfide electrolyte and a halide electrolyte.
10. The battery electrode according to any one of claims 1 to 3, characterized in that: The active layer satisfies at least one of the following conditions (9) to (10): (9) The components of each active layer also include a conductive agent; Optionally, in each active layer, the mass proportion of the conductive agent is independently selected from 0.1wt% to 5wt%; (10) The components of each active layer also include a binder; Optionally, in each active layer, the mass proportion of the binder is independently selected from 0.1wt% to 5wt%.
11. A battery, characterized in that: The battery comprises the battery electrode sheet as claimed in any one of claims 1 to 10.
12. The battery according to claim 11, characterized in that The battery is an all-solid-state battery.
13. An electrical device, characterized in that: The electrical device comprises the battery according to any one of claims 11 to 12.